P64 | EX VIVO EXTRACTION OF GLIOMA SECRETOME: A NOVEL MICROENVIRONMENT-BASED PROTOCOL FOR METABOLIC AND MOLECULAR PROFILING (European Journal of Histochemistry)
Gliomas represent the most frequent primary brain tumors in adults and are marked by considerable molecular and clinical heterogeneity. The 2021 WHO classification of central nervous system tumors identifies three major adult-type diffuse glioma subtypes: astrocytoma IDH-mutant, oligodendroglioma IDHmutant with 1p/19q-codeletion, and glioblastoma IDH-wildtype.1 Despite ongoing advances, treatment resistance and poor prognosis remain major challenges, largely due to intratumoral heterogeneity and the complexity of the tumor microenvironment.2 A promising yet underexplored avenue for patient-centered glioma profiling is the tumor secretome, which includes soluble factors, extracellular vesicles, and metabolites released by both neoplastic and stromal cells.3 Existing studies rely on in vitro models that fail to recapitulate the complexity of tumor-host interactions. To bridge this gap, we established an innovative, standardized ex vivo protocol for secretome isolation directly from glioma tissue. The protocol preserves microenvironmental cues from the operating room to laboratory analysis, ensuring spontaneous secretome release under controlled conditions. Feasibility and performance were assessed in a preliminary cohort of seven adult diffuse glioma patients. Transmission electron microscopy confirmed tissue structural integrity. Proteomic profiling identified 84 cancer-associated proteins within the secretome. Additionally, metabolomic analysis revealed a distinctive signature of small molecules. Notably, glioblastoma IDH-wildtype samples exhibited increased lactate levels, consistent with hypoxia-driven metabolism, and decreased N-acetylaspartate, indicating neuronal loss. Overall, this ex vivo secretome protocol offers a robust and physiologically relevant platform for glioma characterization, with potential applications in biomarker discovery, patient stratification, and the development of personalized therapeutic strategies.